A study on the retention of calcium in calcium-fortified skinless pork longganiza - Tarape, Patty Rigunan; Dumelod, Benelyn Domingo (2000)
ABSTRACT This study was done primarily to develop a calcium-fortified skinless pork longaniza and to assess the retention of calcium in the product before and after cooking. The BAI formulation was fortified with 33% of the Philippine RDA for adolescents for calcium. The sensory properties were determined using descriptive and acceptability tests. Based on Student's t-test at α=0.05, the fortified longaniza differed significantly form the control in most sensory properties. Modification were done resulting in a more acceptable formulation. Production of the fortified longaniza was upscaled from laboratory to bench scale. Sample from three production batches at bench scale were subjected to sensory analysis ANOVA at α=0.05 showed no significant difference among the samples in terms of their sensory attributes thus the production is replicable provided that process and formulation are strictly monitored and followed. Physico-chemical and calcium analysis of the control and the fortified longaniza showed that former has 38.5% moisture, 28.45% crude fat, 21.4% crude protein, 1.88% TAC, 0.195% fiber and 3.5% ash. The latter has 36.8% moisture, 27.25% crude fat, 19.65% crude protein, 1.36% TA, 0.175% fiber and 6.3% ash. A 30-g uncooked and a 25-g cooked fortified longaniza have calcium contents of 32.53% and 32.18%, respectively. The elemental calcium retained in the uncooked fortified longaniza was 95.02%, thus a 4.98% loss of elemental calcium during cooking. A 360-g pack consisting of a dozen of the fortified longaniza costs PhP 43.30 at wholesale and PhP 48.72 at retail.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Sausages; Sausages, Enriched